Methane production and microbial community analysis in the goethite facilitated anaerobic reactors using algal biomass. (1st April 2015) - Tan, Juan; Wang, Jin; Xue, Jun; Liu, Shao-Yang; Peng, Shu-Chuan; Ma, Ding; Chen, Tian-Hu; Yue, Zhengbo
Highlights: Facilitation of goethite enhanced the methane yield of algal biomass. Goethite had a significant influence on the bacterial community. Goethite did not influence the archaeal community. Fatty acids oxidizing bacteria become dominant when suitable goethite was added. Fe 2+ from the reduction of goethite improved the activity of methanogenic archaea. Abstract: Methane has been attracting increasing attention in the area of global carbon cycle and sustainable bioenergy. Interaction between iron containing minerals and microorganism played an important role in the anaerobic transformation of organic substances. In the current paper, change of methane production and microbial community in the goethite facilitated anaerobic digestion process using algal biomass as representative was reported. Results indicated that addition of goethite significantly influenced the bacterial community and methane production. Methane production was improved when both the iron reducing and fatty acids oxidizing bacteria were dominant. Methane production was suppressed when the iron reducing bacteria evolved as the dominant stains in the bacterial community. The results indicated that the generated Fe 2+ from the reduction of goethite could be consumed as a microbial nutrition. Goethite facilitated the syntrophic effects between the fatty acids oxidizing bacteria and the methanogenic microorganism. Results confirmed that supplementation of iron oxides would be a low-cost way to improve the methane production from organic biomass.